A simulation of insertion and retention forces in cantilever hook snap-fit joint - Siti Sarah, Abdul Manan; Law, Ping Chien; Muhammed Nafis, Osman Zahid (IET, 2023)
There are numerous methods for joining plastic parts together, including adhesive bonding, mechanical fastening and snap-fit. Snap-fit is used in this study to assemble plastic parts because it is an effective, cost-effective and fast joining technique. When it comes to snap-fits, there are two options: separable and inseparable. Separable indicates that the pieces may be disassembled effectively without breaking, whereas inseparable means that the plastic parts are permanently joined.This study focuses on cantilever snap-fit since it is widely utilized in the automobile, aerospace and other industries. There are numerous parameters that influence the functionality of snap-fits, particularly the forces of insertion and retention. The parameters are the feature thickness (Tb), beam length (Lb), beam width (Wb), base radius (Rb), mounting (α) and dismounting angle (β). The increase of insertion and retention angle is believed to increase the forces required to joint and disjoint the cantilever hook snap-fit.